REAP: revealing drug tolerant persister cells in cancer using contrast enhanced optical coherence and photoacoustic tomography. (6th April 2021) - Liu, Mengyang; Deloria, Abigail J; Haindl, Richard; Li, Qian; Szakacs, Gergely; Csiszar, Agnes; Schrittwieser, Stefan; Muellner, Paul; Hainberger, Rainer; Pelaz, Beatriz; Polo, Ester; Del Pino, Pablo; et al.
Abstract: Despite chemotherapy, residual tumors often rely on so-called drug tolerant persister (DTP) cells, which evade treatment to give rise to therapy-resistant relapse and refractory disease. Detection of residual tumor cells proves to be challenging because of the rarity and heterogeneity of DTP cells. In the framework of a H2020 project, REAP will gather researchers and engineers from six countries, who will combine their expertise in biology, chemistry, oncology, material sciences, photonics, and electrical and biomedical engineering in the hope of revealing DTPs in cancer using contrast enhanced multimodal optical imaging. Laser sources for photoacoustic microscopy, photoacoustic tomography, and optical coherence tomography will be developed to enable the design of a two-photon laser scanning optical coherence photoacoustic microscopy system and an optical coherence photoacoustic tomography system. Furthermore, novel photoacoustic detectors using micro-ring resonator will be designed and fabricated, granting improved sensitivity and easier integration of multiple optical imaging modalities into a single system. Innovative algorithms will be developed to reconstruct and analyze the images quickly and automatically. With successful implementation of this four-year project, we can not only gain insight into the mechanisms governing DTPs, but also significantly advance the technology readiness level of contrast agents, lasers, sensors, and image analysis software through joint efforts.